2013
DOI: 10.4103/0972-0707.117502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the sealing ability of different obturation systems used over apically separated rotary nickel-titanium files: An in vitro study

Abstract: Aim:The study was designed to investigate the sealing ability of two obturation systems (cold laterally compacted gutta percha and Obtura II) over different apically separated rotary nickel-titanium files (RACE and K3 system) using dye extraction method.Materials and Methods:Sixty-two mandibular premolars were divided into 2 groups of 30 teeth each, and 2 teeth served as negative controls. In Groups A and B, roots were prepared using RACE and K3 system, respectively, and were further subdivided into 4 subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…However, this method has some drawbacks such as voids, incomplete fusion of the gutta‐percha cones, spreader tracts, and lack of surface adaptation (Whitworth, ). In a previous study, it was found that in the CLC technique the master cones have poor adaptation to the irregular coronal surface of the fracture fragments, leading to a gap and more interphases between master cone with coronal fracture end, accessory cones, sealer, and root canal surfaces, which will lead to the formation of voids and consequently more leakage (Hegde, Bashetty, Kumar, Chikkamallaiah, ). Thus, it can be concluded that the sealer layer may not have had a sufficient thickness to seep and penetrate into dentinal tubules at the 1 mm level, and for that reason, the penetration depths and percentage values in the CLC group were the lowest among groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method has some drawbacks such as voids, incomplete fusion of the gutta‐percha cones, spreader tracts, and lack of surface adaptation (Whitworth, ). In a previous study, it was found that in the CLC technique the master cones have poor adaptation to the irregular coronal surface of the fracture fragments, leading to a gap and more interphases between master cone with coronal fracture end, accessory cones, sealer, and root canal surfaces, which will lead to the formation of voids and consequently more leakage (Hegde, Bashetty, Kumar, Chikkamallaiah, ). Thus, it can be concluded that the sealer layer may not have had a sufficient thickness to seep and penetrate into dentinal tubules at the 1 mm level, and for that reason, the penetration depths and percentage values in the CLC group were the lowest among groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Their separation may affect the outcome of treatment, as a retained instrument will likely prevent the three-dimensional obturation (Altundasar et al, 2008). Several methods such as bacterial leakage (Mohammadi & Khademi, 2006;Saunders et al, 2004), dye extraction (Rangappa et al, 2013), fluid filtration (Altundasar et al, 2008), and cone-beam computed tomography (Nagaveni et al, 2017;Singh et al, 2015) have been introduced to evaluate the quality of root canal obturation. Recently, micro-CT has been preferred widely for this purpose (Başer Can et al, 2017;Endal et al, 2018;Huang et al, 2017;Iglecias et al, 2017;Keleş & Keskin, 2020;Kucukkaya Eren et al, 2019;Oh et al, 2016;Somma et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is easy to control length of filling with this technique, it has some drawbacks such as lack of surface adaptation, heterogeneous merger of the gutta-percha cones, spreader tracts and gaps (Whitworth, 2005). It was previously stated that in the CLC technique, the master cone might show a weak adaptation to the coronal surface of the separated file resulting in the formation of gaps between the gutta-percha and the coronal surface of the separated file, thereby causing more microleakage (Rangappa et al, 2013). Consistent with this study, higher volume of voids was detected in samples obturated with CLC technique in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved using a proper chemomechanical preparation of the root canals, which is fundamental for successful endodontic treatment. [ 8 9 ]…”
Section: Discussionmentioning
confidence: 99%